Optimal model‐based design of the twin‐column CaptureSMB process improves capacity utilization and productivity in protein A affinity capture. Issue 1 (18th December 2015) - Baur, Daniel; Angarita, Monica; Müller‐Späth, Thomas; Morbidelli, Massimo
Abstract: Multi‐column chromatographic processes have recently been developed for protein A affinity chromatography to efficiently capture monoclonal antibodies from cell culture supernatant. In this work, the novel twin‐column CaptureSMB process was compared to a batch capture process with dual loading flow rate to identify performance gains. As a case study, the isolation of a monoclonal antibody with the Amsphere JWT‐203 protein A resin was investigated. Using model based optimization, both processes were optimized and compared over a wide range of operating conditions. A trade‐off between productivity and capacity utilization was found, and the resulting pareto‐curves showed that CaptureSMB dominates batch, except at very low productivity values. With a feed titer of 1.2 mg mL −1, CaptureSMB could reach a productivity of up to 19.5 mg mL −1 h −1 experimentally, while maintaining relatively high capacity utilization of 63.8%. On the other hand, at maximum capacity utilization of 95.5%, a productivity of 10.2 mg mL −1 h −1 could be reached. This corresponds to a performance improvement with respect batch operation of about 25% in capacity utilization and 40% in productivity, for given yield and purity. CaptureSMB therefore offers a greatly increased performance over batch capture. Abstract : Protein A chromatography is the main method used for capturing monoclonal antibodies from clarified cell culture supernatant. The twin‐column CaptureSMB process uses internal recycling and sequential loading in order to improve resin capacity utilization, prolong resin lifetime and decrease resin costs. Using model based multi‐objective optimization, optimal ways of operating the process are identified and compared to state of the art batch capture.